Do infanticides occur in harem-forming equids? A test with long-term sociodemographic data in wild plains zebras. (July 2021) - Vitet, Camille; Duncan, Patrick; Ganswindt, Andre; Mabika, Cheryl; Chamaillé-Jammes, Simon
Abstract : Social dynamics can play a major role in shaping the population ecology and evolutionary trajectory of a species. This is, for instance, the case in species known to experience infanticide when a dominant male is replaced by another. Infanticide by males has been observed in many taxa, mostly in species that breed year-round and in which a few males monopolize reproduction. In such species, infanticide often occurs after take-overs of breeding groups, and the frequency of take-overs often increases with increasing female group size, therefore raising the risk of infanticide in larger groups. Among ungulates, male infanticide has been reported mostly in harem-forming equids in captive populations, usually following harem-male turnover. In this study, we empirically tested in the wild whether the rate of stallion (i.e. harem-male) turnover increases with the number of reproductive females in harems, and whether these events reduce foal survival. We used a long-term study of wild plains zebra, Equus quagga, in Hwange National Park, Zimbabwe, where, for more than 15 years, stallion turnovers have been recorded and accurate data on pregnancy obtained by hormone assays. We show that stallion turnovers were frequent and, as expected, particularly in harems with many reproductive females. We found that foal survival did not differ significantly between situations when a stallion turnover occurred shortly before or after their birth and when it did not. This result was consistent with the fact that no attacks by stallions on foals of their group or forced matings were observed during the study. Our study offers rare data showing that if male infanticide occurs in wild plains zebra, this should be rare, and has no important consequences for foal survival at the population level. Highlights: In harem-forming equids, infanticide might occur when a stallion is replaced. Yet, no infanticides were observed during a >10-year study of wild plains zebras. Stallion turnovers were frequent, notably in harems with many reproductive females. Foal survival was not reduced when a stallion turnover occurred. Infanticide, if it occurs, has a negligible demographic impact on this population.